2021
DOI: 10.1177/07067437211025217
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Psychological Distress in Health-care Workers during and after the First Wave of COVID-19: A Canadian Longitudinal Study: Évaluation de la Détresse Psychologique Chez Les Travailleurs de la Santé Durant et Après la Première Vague de la COVID-19: une étude longitudinale canadienne

Abstract: Objectives: Health-care workers (HCW) exposed to COVID-19 are at risk of experiencing psychological distress. Although several cross-sectional studies have been carried out, a longitudinal perspective is needed to better understand the evolution of psychological distress indicators within this population. The objectives of this study were to assess the evolution of psychological distress and to identify psychological distress trajectories of Canadian HCW during and after the first wave of COVID-19. Method: Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

16
43
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(60 citation statements)
references
References 32 publications
16
43
1
Order By: Relevance
“…Dufour and colleagues' work investigated the frequency of psychological distress among healthcare workers (HW) in the province of Quebec during and after the first wave of COVID-19 pandemic. 1 Authors reported peak point prevalence of mental health symptoms in HW of 22.2% for post-traumatic stress, 29.9% for depression and 26.9% for anxiety, consistent with similar data collected around the World. 2 These findings are mirrored in a recent cross-sectional survey conducted in Abu Dhabi in the United Arab Emirates (UAE) at the zenith of the first wave of the pandemic, suggesting that an overall 39% of HW were affected by symptoms of depression, anxiety and stress, 13% of them severely.…”
supporting
confidence: 86%
“…Dufour and colleagues' work investigated the frequency of psychological distress among healthcare workers (HW) in the province of Quebec during and after the first wave of COVID-19 pandemic. 1 Authors reported peak point prevalence of mental health symptoms in HW of 22.2% for post-traumatic stress, 29.9% for depression and 26.9% for anxiety, consistent with similar data collected around the World. 2 These findings are mirrored in a recent cross-sectional survey conducted in Abu Dhabi in the United Arab Emirates (UAE) at the zenith of the first wave of the pandemic, suggesting that an overall 39% of HW were affected by symptoms of depression, anxiety and stress, 13% of them severely.…”
supporting
confidence: 86%
“…The analysis of stress and mental health at various times of the pandemic and after its conclusion will help to disentangle the effect of the epidemic from that of other common stressors in health care activities. Several epidemiological studies based on repeated cross-sectional models have been announced or have published baseline reports [ 59 , 60 , 61 , 62 , 63 ]. This study is the first to document the mental health differences of HCWs at the start of the pandemic and after ten months, when the second wave had its effects and vaccines were not yet available.…”
Section: Discussionmentioning
confidence: 99%
“…In spite of the increasing publication of longitudinal studies that have analyzed psychological impact of COVID-19 on the mental health status of the HCW, no reliable conclusions have been drawn ( Dufour et al, 2021 ; Sasaki et al, 2021 ). Nevertheless, previous longitudinal studies examining mental health consequences among professionals facing previous major disasters showed a high prevalence of psychological effects among this population ( Fullerton et al, 2004 ).…”
Section: Introductionmentioning
confidence: 99%